2018
DOI: 10.3390/insects9020042
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Penetration Ability of Plodia interpunctella (Hübner) (Lepidoptera: Pyralidae) Larvae into Multilayer Polypropylene Packages

Abstract: The larvae of the Indian meal moth, Plodia interpunctella (Hübner), can invade or penetrate packaging materials and infest food products. Energy bars with three polypropylene packaging types were challenged with eggs (first instars), third instars, and fifth instars of P. interpunctella to determine package resistance at 28 °C and 65% r.h. The packing types were also challenged with two male and two female pupae of P. interpunctella under similar conditions in order to determine which package provided the grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…2005; Liu & Ho 1999; Scheff et al . 2018). For instance, T. castaneum has been reported to be one of the most common insects attacking cocoa beans globally (Abdullahi et al .…”
Section: Introductionmentioning
confidence: 99%
“…2005; Liu & Ho 1999; Scheff et al . 2018). For instance, T. castaneum has been reported to be one of the most common insects attacking cocoa beans globally (Abdullahi et al .…”
Section: Introductionmentioning
confidence: 99%
“…In the CO1 amplicons of the Eriocheir sinensis (FH) and JHC (DNA mixture), several reads were identified as Philodina roseola [53], which is often used in crab breeding and is considered as an endogenous species. In contrast, in a few reads from exogenous animal species, such as Plodia interpunctella [54], an insect commonly seen in storage spots, and Tortricidae sp. [55,56], a class of harmful insects in agriculture field, was found in the powders.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been documented that C. cautella larvae can penetrate through a variety of packing materials, such as cellophane, polyethylene, paper material, polyvinylchloride and polypropylene films [80][81][82]. P. interpunctella, a closely related lepidopteran species that shares certain behavioural characteristics with C. cautella [16] is also able to penetrate through polyethylene [83,84], but this ability differs with the age of larvae [81,82,85] and the thickness of material [82,85]. By contrast, larvae of P. interpunctella and Trogoderma variabile Ballion (Coleoptera: Dermestidae) cannot penetrate through methoprene-treated foil packaging [84].…”
Section: Discussionmentioning
confidence: 99%
“…P. interpunctella, a closely related lepidopteran species that shares certain behavioural characteristics with C. cautella [16] is also able to penetrate through polyethylene [83,84], but this ability differs with the age of larvae [81,82,85] and the thickness of material [82,85]. By contrast, larvae of P. interpunctella and Trogoderma variabile Ballion (Coleoptera: Dermestidae) cannot penetrate through methoprene-treated foil packaging [84]. Some other studies have revealed that the few warehouse beetle T. variabile larvae that were able to penetrate methoprene-treated foil experienced deformities in the adult stage [86].…”
Section: Discussionmentioning
confidence: 99%